Reliability-constrained optimal sizing and rechargeable battery selection for improved load distribution in a fuel-cell hybrid railway propulsion system. (15th September 2019) - Abbas, Mazhar; Cho, Inho; Kim, Jonghoon
Highlights: Fuel cell – battery hybridization for railway propulsion system is discussed. The load is distributed between power sources with objective of mitigation of constraints. The actual load data of subway train is used for realization of actual conditions. Conditions are proposed for reliable sizing and optimized selection of battery. Certain developed batteries are evaluated based on proposed conditions. Abstract: Limiting the increase of global temperature requires electrification of the railway transport, which is relatively a distinct mode of transport in terms of economy, business and socialization of a country. However, battery complemented railway transport systems such as fuel cell hybrid railway propulsion systems are constrained by the high cost of the battery, and suboptimal performance of the fuel cell under varying loads. Optimized selection of battery can reduce its costs associated with sizing, life and utilization. Similarly, managing the load distribution between the battery and fuel cell can reduce the load variations concern for fuel cell. In this study, model-based selective characterization of the battery and fuel cell is done to identify the optimal features and constraints. Following characterization, the load allocation to battery and fuel cell is determined with the targets of collaborative utilization of optimal features and mitigation of constraints. Subsequently, considering this load allocation and results of characterization, conditions are proposed for reliable sizing and optimized selection of battery. The significance of the proposed conditions in reliable sizing is explored. Based on these conditions, certain commercially developed batteries are evaluated for optimized selection of battery. The results signify this study as a foundation for research on the reliable sizing and optimized selection of battery in fuel cell hybrid railway propulsion systems.